2013
DOI: 10.1002/app.40054
|View full text |Cite
|
Sign up to set email alerts
|

Reactive, intumescent, halogen‐free flame retardant for polypropylene

Abstract: A reactive, intumescent, halogen-free flame retardant, 2-({9- [(4,6-diamino-1,3,5-triazin-2-yl)amino]-3,9-dioxido-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecan-3-yl}oxy)ethyl methacrylate (EADP), was synthesized through a simple three-step reaction from phosphorus oxychloride, pentaerythritol, hydroxyethyl methacrylate, and melamine. EADP exhibited excellent thermal stability and char-forming ability, as revealed by thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The TGA results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Furthermore, the T co and T cp values of the PP/EADP‐30 composite were higher than those of PP/MAPP‐30 by 4.86 and 4.57°C, respectively; this indicated that EADP was more beneficial for heterogeneous nucleation. Because a considerable number of EADP could be bonded to the PP chains during reactive blending and afford good compatibility between PP and EADP, this reduced the free energy of the nucleation process and increased the rate of crystallization …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the T co and T cp values of the PP/EADP‐30 composite were higher than those of PP/MAPP‐30 by 4.86 and 4.57°C, respectively; this indicated that EADP was more beneficial for heterogeneous nucleation. Because a considerable number of EADP could be bonded to the PP chains during reactive blending and afford good compatibility between PP and EADP, this reduced the free energy of the nucleation process and increased the rate of crystallization …”
Section: Resultsmentioning
confidence: 99%
“…In particular, β‐form crystals, which have the potential to improve the impact toughness, were formed in the PP/EADP composites . As a result, the PP/EADP composites not only had excellent flame‐retardant properties but also presented good comprehensive mechanical properties …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the increased band at about 1620 cm −1 was ascribed to C=C structure [24,25], which was also produced by PEPA and could promote the formation of thermostable residue [19]. When the temperature reached up to 400 ∘ C, there was a new peak around 1100 cm −1 appearing, which corresponded to P-N absorption [26], indicating that the phosphorus-containing compounds could further crosslink with the triazine oligomer produced by MPP [3,27]. With the further increase of pyrolysis temperature, the intensities of the bands at 3200-3500 cm −1 ( N-H and O-H ) decreased gradually and nearly disappeared at 550 ∘ C to 650 ∘ C. However, the bands at 1075 cm −1 ( P-O-C ), 1100 cm −1 ( P-N ), and 1485 cm −1 ( C=N ) were almost invariable.…”
Section: Thermal Behaviormentioning
confidence: 97%